Amplitude‐integrated electroencephalography in male newborns <30 weeks' of gestation and unfavourable neurodevelopmental outcome at three years is less mature when compared to females. (30th July 2013) - Olischar, Monika; Waldhör, Thomas; Berger, Angelika; Fuiko, Renate; Weninger, Manfred; Klebermass‐Schrehof, Katrin
Abstract: Aim: To investigate gender‐related differences in amplitude‐integrated electroencephalography (aEEG) associated with neurodevelopmental outcome at 3 years. Methods: Preterms born <30 weeks' gestational age between 2000 and 2002 were prospectively included. aEEGs obtained within the first 2 weeks of life were classified according to aEEG composite scores – including background pattern, sleep–wake cycling (SWC) and seizure activity. Neurodevelopmental outcome was assessed at 3 years of age. Results: Neurodevelopmental outcome data was available for 148 of 264 eligible infants – 64 showed a normal outcome and 84 an impaired outcome. A logistic regression model revealed a significant independent influence of IVH, analgetic/sedative/anticonvulsant medication, gestational age and gender on aEEG composite scores. Odds ratios for having an abnormal aEEG composite score within the first 2 weeks of life for 'female sex', 'no IVH', 'no medication' and 'gestational age' were calculated. aEEG did not differ between males and females with normal outcomes. In patients with abnormal outcome, however, male preterms showed more burst‐suppression patterns and less SWC when compared with female preterms. Conclusion: Being male with an abnormal outcome at 3 years of age is reflected by a less mature early aEEG when compared with the one of females. This association is independent of IVH and medication and was less evident with increasing gestational age.